2018
DOI: 10.1074/jbc.ra118.001987
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor scleraxis vitally contributes to progenitor lineage direction in wound healing of adult tendon in mice

Abstract: Tendon is a dense connective tissue that transmits high mechanical forces from skeletal muscle to bone. The transcription factor scleraxis (Scx) is a highly specific marker of both precursor and mature tendon cells (tenocytes). Mice lacking scx exhibit a specific and virtually complete loss of tendons during development. However, the functional contribution of Scx to wound healing in adult tendon has not yet been fully characterized. Here, using ScxGFP-tracking and loss-of-function systems, we show in an adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
125
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(131 citation statements)
references
References 61 publications
(88 reference statements)
6
125
0
Order By: Relevance
“…A trace of adult Scx Lin revealed that not all tenocytes are Scx Lin during homeostasis, providing evidence that tenocytes are not a homogenous population. It has previously been shown that Scx-GFP mice (19) label most, but not all, tendon cells (8). In this work, we have shown that Scx-GFP mice label ;90% of intrinsic flexor tendon cells (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…A trace of adult Scx Lin revealed that not all tenocytes are Scx Lin during homeostasis, providing evidence that tenocytes are not a homogenous population. It has previously been shown that Scx-GFP mice (19) label most, but not all, tendon cells (8). In this work, we have shown that Scx-GFP mice label ;90% of intrinsic flexor tendon cells (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 50%
“…Scale bars, 100 mm (B), 20 mm (C, D). *P , 0.05. that tendon cells lose Scx expression shortly after acute injury (8) and that Scx expression is mechanosensitive (17). Traces of Scx 022 and Scx 527 populations revealed differential Scx expression patterns during healing, with Scx 022 exhibiting fewer Scx Ai9 cells relative to Scx Lin and Scx 527 traces, and an absence of Scx Ai9 cells within the scar tissue.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, a recent study by Sakabe et al . demonstrated that a partial Achilles tendon transection had Scx+ cells within the defect site by day 14 post-injury [8]. This suggests that keeping the cut ends of the tendon near one another and the maintenance of tensile force across the defect may be necessary for localization of Scx+ cells within the defect.…”
Section: Discussionmentioning
confidence: 99%
“…Scx is a basic helix-loop-helix transcription factor that directs expression of extracellular matrix components and is necessary for the proper development of force-transmitting tendons [4-6]. The localization of Scx+ cells during healing differs greatly between specific tendons and injury models, with some studies showing Scx+ cells localized at and bridging the defect site [7, 8] while others exhibit a complete absence of Scx+ cells within the scar [3]. No studies have extensively characterized Scx lineage cell localization in either a flexor tendon injury model or a model of complete transection and repair.…”
Section: Introductionmentioning
confidence: 99%